Exploring Indonesia’s Artisanal Fashion Potential: A Case Study of Meraki Studios Subtitle - Nursari, Faradillah; Rima Febriani; Widia Nur Utami (Telkom University, 2023)
As a country rich in natural and human resources, Indonesia has the potential to develop artisanal fashion. Hand skills and mastery of traditional techniques originating from various local wisdom in Indonesia are some supporting factors for developing local artisan products. Since ancient times, people in Indonesia have used production aspects involving artisan hand skills to make functional, commercial, and non-commercial products. Artisanal fashion is considered by many as a sustainable approach in the fashion industry due to its ethical and low environmental impact. However, the study of artisan fashion products has not been widely discussed in the academic realm. This study focuses on understanding artisan fashion products through local fashion brand Meraki Studios case studies. The approach used in this research is descriptive qualitative, which is done by collecting data through observations, interviews, and literature studies regarding the meaning of artisanal fashion, the practice of artisanal fashion, and how Meraki Studios' practice in artisanal fashion is applied in their design and production process.